Surirella caljoniana Solak & Cocquyt & Hamilton & Holmes & Yilmaz & Kesbiç 2023, sp. nov. - Solak, Cüneyt Nadir; Cocquyt, Christine; Hamilton, Paul B.; Holmes, Joe; Yilmaz, Elif; Kesbiç, Işil (Zenodo, 2023)
Surirella caljoniana sp. nov. Solak, Cocquyt & Hamilton (LM: Figs 2–6; SEM: Figs 7–16) Description LM. Valves elliptical, heteropolar with broadly rounded headpole and narrowly rounded to rarely protracted footpole. Valve length: 37.0–47.0 µm, width: 15.0–17.5 µm, length width ratio: 2.3–2.7 (n=8). Valve face slightly concentrically undulate. Striae clearly visible in LM, 18–21 in 10 µm, parallel at mid-valve, radiate near apices. Striae alternate, extending from the axial area to the valve face margin. Sometimes a shorter stria intercalated with longer striae near the apices or near valve face margin. Axial area narrow, continuous from one pole to the other, often weakly irregularly wavy. Fibulae extend out up to one quarter the width of the valve face, 3–4 in 10 µm. SEM—External view (Figs 7–11): Valve face with robust costae and ornamented with reticulate thickenings parallel to apical axis (Figs 7, 8). Costae 18 in 10 µm of which only those close to apices reach axial area. Axial area undulating in the middle portion of valve face, with small, rounded, isolated poroids (Figs 10, 11). Striae multiseriate, composed of 4–6, mostly 4 rows of elongated slit-shaped poroids and irregular fimbriate silica protrusions from the costae parallel to the apical axis (Fig. 8). Striae usually parallel to apical axis but sometimes irregularly placed and often closer to edge of valve (fig. 9). Fimbriate silica protrusions scattered within the striae between areolae (Figs 8–11). Raphe located on a shallow keel. Top of keel smooth, without perforations or ornamentation. Terminal raphe fissures on both apices straight and not enlarged (figs 10, 11). Internal view (Figs 12–16): Areolae multiseriate within striae, rounded, 90–110 in 10 µm (Figs 12–14). Portulae almost rectangular in shape, of different sizes, smallest ones next to fibulae, and (1) 3 to 4 between two fibulae; 2 or 3 silica ribs and 1 to 3 striae per portula. Striae near edge of fibulae mostly shorter than others and of same length or somewhat longer than fibulae on internal valve face (Figs 14). No striae present on fibulae (Fig. 13). On side of axial area, a shortened stria may be present opposite fibula. Terminal raphe fissures near foot pole slightly deflected towards valve face but continuous near head pole (Figs 15, 16). Type:— TÜRKIYE. Sivas, Göydün Spring, collected as an epilithic sample (39°48’34.96’’N, 37°12’30.85’’E, 1277 m a.s.l.), C.N. SOLAK, 14 September 2020 (holotype CANA 129682, Nature Museum of Canada, Canada) Valve representing the holotype slide is here illustrated in Fig. 5; isotype TR_SVS_Göydün Spring_ September 2020 _EPL deposited at Kütahya Dumlupınar University, Turkye; isotype BR 4763, Meise Botanic Garden, Belgium) Registration:— http://phycobank.org/103729 Etymology:— The species is dedicated to the late Adolf CALJON, husband of Christine Cocquyt, in recognition of his important contributions to algal studies. Distribution:— Observed from the type locality. Differential diagnosis:— Surirella brebissonii Krammer & Lange-Bertalot (1987: 82, plate 126: 2), S. brebissonii var. kuetzingii Krammer & Lange-Bertalot (1987: 85, plate 126: 3–11), S. lacrimula J.D.English in English and Potapova (2012: 22, figs 45–54), S. neglecta Reichardt (2012: 30, figs 58–67) and S. subsalsa W. Smith (1853: 34, fig. 259) are similar in morphology and general shape. Among them, Surirella brebissonii var. kuetzingii is the most similar however, S. caljoniana has an oval-elliptic, slightly heteropolar outline, larger length/width ratio and narrowly rounded to slightly protracted foot pole. S. brebissonii var. kuetzingii has an ovate outline, narrower length/width ratio and higher costa density. S. brebissonii has a broadly elliptic to almost rounded outline with higher costa density. S. lacrimula has an ovate outline with broadly rounded head pole and rounded to narrowly cuneate foot pole. S. neglecta has a similar outline (oval-elliptic) but with a broad head pole and cuneate foot pole. S. subsalsa has oval to linear-oval outline with narrowly rounded poles. Ecology:— The general limnology of Sakarbaþı limnocrene spring was pH– 7.8–7.9, EC (μS.cm –1)– 545–575, DO (mg.L –1)– 5.2–6.1, T (℃) – 21.4–22.9. Associated diatom flora:— In Göydün Spring, a new Halamphora species and Ctenophora sp. were dominant taxa while S. caljoniana was rare. Unidentified species of Achnanthidium Kützing, Cymbella Agardh, Crenotia Wojtal, Surirella Turpin and Halamphora Levkov were other frequent taxa in the sample.

Published as part of Solak, Cüneyt Nadir, Cocquyt, Christine, Hamilton, Paul B., Holmes, Joe, Yilmaz, Elif & Kesbiç, Işil, 2023, A new diatom (Surirellaceae: Bacillariophyta) species-Surirella caljoniana sp. nov. - in Göydün Spring, Sivas in Eastern Anatolia, Republic of Türkiye, pp. 99-108 in Phytotaxa 595 (1) on pages 101-102, DOI: 10.11646/phytotaxa.595.1.7, http://zenodo.org/record/7889581
Keywords: Chromista; Bacillariophyceae; Surirellaceae; Surirella caljoniana; Surirellales; Biodiversity; Surirella; Bacillariophyta; Taxonomy; 15. Life on land